Online Marketing Strategy in Tourism Village Using Videography - Praswati, Aflit Nuryulia; Utami, Ayu Sri; Fatahuddin, Amir; Prijanto, Tulus (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2017)
Online marketing cannot be underestimated in the creative industries. It can be a powerful strategy to introduce and popularize the offered product or service. Moreover, such a strategy can be learned and done easily with the suitable knowledge. However, only as small number of creative industries in Sukoharjo Regency has applied this marketing strategy. The actors in creative industries still use simple methods, such as verbal marketing, direct selling to the market and direct order from customers who come to the production site. Such methods make the products and services are only used by people around Sukoharjo. Limitations of the marketing area result in lessoptimal revenue. To solve some problems in the creative industries in Sukoharjo, the trainings on how to expand the marketing area through Internet or online, and the trainings of online advertising in the form of videographyare required. Videography will provide the information about the offered products or services for the customer or prospect customers. The training was conducted in one of the creative industrial centre in Sukoharjo. As an attempt to expand marketing, videography as an online marketing advertisement is expected to help the actors of creative industries in introducing their products/services to the public and increasing public’s interest to use the products/services that can ultimately increase revenue.